A New Method to Prove and Find Analytic Inequalities - Xiao-Ming Zhang; Bo-Yan Xi; Yu-Ming Chu (Abstract and Applied Analysis)
We present a new method to study analytic inequalities. As for its applications, we prove the well-known Hölder inequality and establish several new analytic inequalities.